2018
DOI: 10.1101/503912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genotypic variation in root distribution changes and physiological responses of sugarcane induced by drought stress

Abstract: 1Drought is an important factor reducing yield and quality of sugarcane. Root growth and 1 2 physiological traits are important for maximizing water uptake to improve drought resistance. 3This study compared the root, shoot and physiological traits under drought stress (DS) and 1 4 well-watered (WW) conditions of various sugarcane varieties grown in rhizoboxes in a 1 5 greenhouse at the Field Crops Research Station of Khon Kaen University, Khon Kaen, 1 6Thailand. Data were recorded for the root, shoot and phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It was determined the relative Chl content. A measurement of Chl was made between the hours of 9:00 and 12:00 am using a SPAD (Soil Plant Analytical Development) chlorophyll meter reading (SCMR) SPAD502-Plus (Konica Minolta, Tokyo, Japan), according to Namwongsa et al (2018). After calibrating, SPAD meter was shut by squeezing it without inserting a leaf, measurements were taken for each control and treated on the second or third fully developed leaf from the top of the main stem.…”
Section: Physiological Parameters 331 Chlorophyllmentioning
confidence: 99%
“…It was determined the relative Chl content. A measurement of Chl was made between the hours of 9:00 and 12:00 am using a SPAD (Soil Plant Analytical Development) chlorophyll meter reading (SCMR) SPAD502-Plus (Konica Minolta, Tokyo, Japan), according to Namwongsa et al (2018). After calibrating, SPAD meter was shut by squeezing it without inserting a leaf, measurements were taken for each control and treated on the second or third fully developed leaf from the top of the main stem.…”
Section: Physiological Parameters 331 Chlorophyllmentioning
confidence: 99%
“…Maintenance of high-water uptake under drought stress is also facilitated by improved root/shoot ratio in drought-tolerant cultivars [18]. Namwongsa et al [19] observed that roots of sugarcane genotypes showed reduced growth in the upper soil layers (0 to 30 cm) in response to drought stress, whereas growth in the lower soil layers (below 30 cm) increased substantially. Under water-limited conditions, assimilated partitioning towards the roots area relatively higher than to shoots [20].…”
Section: Root Biologymentioning
confidence: 99%